2013
DOI: 10.1097/scs.0b013e3182a23535
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Hemorrhage of a Facial Neurofibroma

Abstract: A 50-year-old man with neurofibromatosis type 1 presented to the emergency department after a spontaneous hemorrhage into a facial plexiform neurofibroma. An emergent selective angiography of the external carotid artery was performed with Onyx embolization of the origin of the internal maxillary artery as well as the superficial temporal artery to minimize arterial bleeding during the subsequent operative hematoma evacuation. This technique was aimed to control blood loss during the surgical procedure and redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…17 A wide variety of cases with intrathoracic, cerebral, subcutaneous, or retroperitoneal involvement have been described in the literature, with a mean patient age of 38 years (range, 22-54 years). [17][18][19][20][21][22][23][24][25] These cases range from a deadly retropharyngeal hematoma due to a plexiform neurofibroma at the site of prior surgical intervention 18 to successful preoperative embolization and subsequent surgical intervention in a plexiform neurofibroma of the left posterior neck with spontaneous expanding hemorrhage. 17 Between these extremes, Tomei et al 19 reported a nearly fatal, acutely expanding, hemorrhagic facial plexiform neurofibroma, in which bleeding was controlled surgically after extensive preoperative embolization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 A wide variety of cases with intrathoracic, cerebral, subcutaneous, or retroperitoneal involvement have been described in the literature, with a mean patient age of 38 years (range, 22-54 years). [17][18][19][20][21][22][23][24][25] These cases range from a deadly retropharyngeal hematoma due to a plexiform neurofibroma at the site of prior surgical intervention 18 to successful preoperative embolization and subsequent surgical intervention in a plexiform neurofibroma of the left posterior neck with spontaneous expanding hemorrhage. 17 Between these extremes, Tomei et al 19 reported a nearly fatal, acutely expanding, hemorrhagic facial plexiform neurofibroma, in which bleeding was controlled surgically after extensive preoperative embolization.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25] These cases range from a deadly retropharyngeal hematoma due to a plexiform neurofibroma at the site of prior surgical intervention 18 to successful preoperative embolization and subsequent surgical intervention in a plexiform neurofibroma of the left posterior neck with spontaneous expanding hemorrhage. 17 Between these extremes, Tomei et al 19 reported a nearly fatal, acutely expanding, hemorrhagic facial plexiform neurofibroma, in which bleeding was controlled surgically after extensive preoperative embolization. A theme that has emerged from multiple reports is the possibility of bleeding complications at the site of prior (recent or remote) surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the risk of PHE, promising outcomes of preoperative TAE [7][8][9][10][11][12] and other intraoperative devices, including electric coagulation devices [17] and Tsukisui devices [18], have been reported. However, the indication of preoperative TAE for PNs is often determined only by surgeons' experience, and information on whether PNs should be treated by embolization, such as tumor size, is limited.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the risk of hemorrhage, several attempts have been made to perform preoperative transcatheter arterial embolization (TAE) to reduce the risk of perioperative hemorrhagic events (PHE), including intraoperative massive blood loss and postoperative surgical site hematoma [7][8][9][10][11][12]. Although these previous reports have demonstrated promising efficacy in reducing PHE, systematic and statistical analyses of the incidence of PHE with and without preoperative TAE have not been conducted.…”
Section: Introductionmentioning
confidence: 99%